2016
DOI: 10.1007/s00894-016-3015-z
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches to find the active binding sites of biological targets against busulfan

Abstract: Determination of electrophilic and nucleophilic sites of a molecule is the primary task to find the active sites of the lead molecule. In the present study, the active sites of busulfan have been predicted by molecular electrostatic potential surface and Fukui function analysis with the help of dispersion corrected density functional theory. Similarly, the identification of active binding sites of the proteins against lead compound plays a vital role in the field of drug discovery. Rigid and flexible molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…However, resistance to this drug and its toxicity are major problems in the treatment of APL (Tomita et al, ). Plant‐derived bioactive compounds have been shown in numerous studies to exert a variety of antitumor actions, making them potential candidates for adjuvant therapy of different types of cancer (Karthick & Tandon, ; Mirzaei et al, ; Momtazi et al, ; Moradzadeh, Sadeghnia, Tabarraei, & Sahebkar, ). In the previous study, we showed that EGCG increased apoptosis and inhibited telomerase activity in breast cancer cells (Moradzadeh, Sadeghnia, Tabarraei, & Sahebkar, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, resistance to this drug and its toxicity are major problems in the treatment of APL (Tomita et al, ). Plant‐derived bioactive compounds have been shown in numerous studies to exert a variety of antitumor actions, making them potential candidates for adjuvant therapy of different types of cancer (Karthick & Tandon, ; Mirzaei et al, ; Momtazi et al, ; Moradzadeh, Sadeghnia, Tabarraei, & Sahebkar, ). In the previous study, we showed that EGCG increased apoptosis and inhibited telomerase activity in breast cancer cells (Moradzadeh, Sadeghnia, Tabarraei, & Sahebkar, ).…”
Section: Discussionmentioning
confidence: 99%
“…relative nucleophilicity ( f k − /f k + ) of BPPTS and DPPH were calculated. 28 The site with the maximal value of f k + /f k − is the most expected site to be attacked by nucleophilic attack and those with the highest value of f k − /f k + have the greatest chances of electrophilic attack. The global electrophilicity index (ω) is a measure of energy stabilization when the system acquires an additional electronic charge from the surroundings.…”
Section: Resultsmentioning
confidence: 99%
“…The three‐dimensional structure of CD133 and DKK3 protein was predicted by using the Phyre server (http://www.sbg.bio.ic.ac.uk/phyre2). The interaction between DKK3 or CD133 and NKG2D protein was analyzed by HEX 8.0.0 …”
Section: Methodsmentioning
confidence: 99%